Preparing for the Pandemic: Strengthening Epidemiological Investigations in The Republic of Korea, 2015-20 - Yechan, Moon (KDI School of Public Policy and Management, 2021)
When the epidemic of Middle East Respiratory Syndrome (MERS) hit the Republic of Korea in 2015, the government found that its infectious disease management system was woefully inadequate. At the time, the government faced legal limitations in collecting information to track how viruses spread from person to person and medical information (such as hospital admissions) about those infected. In addition, the country’s epidemiological investigators—the officials tasked with tracking the spread of the virus—did not have the capacity to manage a large outbreak. As a result of these constraints, MERS continued to spread through the population, infecting nearly 200 people nationwide. Following the MERS epidemic—which resulted in 38 deaths—the government realized it needed to establish a legal foundation for epidemiological investigation and boost capacity. In 2015, South Korea revised laws and laid the foundations for improved epidemiological investigations. When COVID-19 arrived in Korea in January 2020, epidemiological investigators were better prepared to track infections and prevent a widespread outbreak of the new infectious disease. Korea's case conveys the importance of a strong institutional basis for virus management.
Keywords: Preventing the spread of infectious disease; Lack of Regulation or Legislation; Lack of Skilled Human Resources